Respon pertumbuhan dan produksi padi beras merah (Oryza nivara) terhadap cekaman kekeringan pada fase pertumbuhan berbeda dan pemupukan nanosilika - Rita Sugiarto; Budi Adi Kristanto; Dwi Retno Lukiwati (Journal of Agro Complex, 2018)
The purpose of this research was to analyze the response of growth and production of red rice (Oryza nivara) under drought and nanosilica fertilization condition. This research was conducted in Greenhouse and Laboratory of and Plant Physiology and Breeding of at Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang from April to July 2017. The research was arranged using completely randomized factorial design. The first factor was drought stress (control, drought 20-35 DAP (Days After Planting), 40-55 DAP and 55-70 DAP). The second factor was the use of nanosilika fertilizers (without nanosilika, with nanosilica). The data were analyzed by anova and followed by Duncan’s Multiple Range Test (DMRT). The results showed that the drought stress during tiller production stage decreased the total number of tillers, productive tillers and grain weight per clump, but not in weight of one thousand seeds. Drought stress during flowering stage and seed filling only decreases the weight of one thousand seeds. Application of nanosilica increases the number of productive tillers and the weight of grain per hill. There was no interaction between drought stress treatment and nanosilika fertilization. Keywords: red rice, production, drought, nanosilica.